What place for prolonged-release buprenorphine depot-formulation Buvidal® in the treatment arsenal of opioid dependence? Insights from the French experience on buprenorphine. (2nd September 2019) - Vorspan, Florence; Hjelmström, Peter; Simon, Nicolas; Benyamina, Amine; Dervaux, Alain; Brousse, Georges; Jamain, Thierry; Kosim, Margaux; Rolland, Benjamin
ABSTRACT: Introduction : Since the 1990s, opioid maintenance treatments (OMTs), i.e. mostly methadone and buprenorphine, have represented the therapeutic cornerstone of opioid dependence. In France, the public health strategy on opioid dependence, identified here as the 'French model', has consisted of offering a facilitated access to buprenorphine, to reach a large treatment coverage and reduce opioid-related mortality. Areas covered : Recently, a new formulation of subcutaneous buprenorphine depot (Buvidal®) has been approved in Europe for treatment of opioid dependence. The place of Buvidal® among the pre-existing arsenal of OMTs is discussed in the light of the pharmacological specificities of this new formulation, and with the particular standpoint of the French model on opioid dependence. Expert opinion : Buvidal® could constitute a promising treatment option mainly in case of: 1) OMT initiation, including in non-specialized addiction medicine care; 2) Discharge from prison or hospital; Diversion/misuse of 3) buprenorphine or 4) methadone; 5) Clinically stabilized patients wishing to avoid daily oral taking of the medication. As such, this new formulation should be highly accessible, which will require specific pathways through care as the product is intended to be administered by a healthcare professional.